Multimodal Location Estimation of Videos and Images - Choi, Jaeyoung; Friedland, Gerald (Springer International Publishing : Imprint: Springer, 2015)
This book presents an overview of the field of multimodal location estimation, i.e. using acoustic, visual, and/or textual cues to estimate the shown location of a video recording. The authors' sample research results in this field in a unified way integrating research work on this topic that focuses on different modalities, viewpoints, and applications. The book describes fundamental methods of acoustic, visual, textual, social graph, and metadata processing as well as multimodal integration methods used for location estimation. In addition, the text covers benchmark metrics and explores the limits of the technology based on a human baseline. ·         Discusses localization of multimedia data; ·         Examines fundamental methods of establishing location metadata for images and videos (other than GPS tagging); ·         Covers Data-Driven as well as Semantic Location Estimation.